Additive manufacturing oriented parametric topology optimization design and numerical analysis of steel joints in gridshell structures - Zuo, Wenkang (2023)
Additive manufacturing (AM) oriented joint topology optimization (TO) is a novel integrated computer-aided structural design and construction paradigm for spatial structures. This research proposed a complete computer-aided workflow for the TO design, numerical analysis and AM of steel joints in gridshell structures. A fully parametric TO design method for joints in gridshell structures was established based on the Grasshopper platform. The joints were automatically generated based on subdivision surface technology and then optimized using the bi-directional evolutionary structural optimization (BESO) algorithm. The structural performance of the optimized joints in terms of compliance, maximum displacement and maximum stress was studied through finite element analysis. The influences of various design parameters, including the loading condition, target volume and filter radius, on the structural performance of the optimized joints were investigated. The target volume was confirmed to have significant effect on the joint structural behaviour while the filter radius was found to affect the branch features of optimized joint. A practical design example of steel joints in single-layer cylindrical gridshell structure was presented to demonstrate the feasibility and validity of the proposed workflow. A typical optimized joint made of 316L stainless steel was additively manufactured using selective laser melting.